Uso de energia solar fotovoltaica e de biodigestor na comunidade Três Unidos: estudo de caso - Lima, Alice Amazonas (Brasil, 2022)
The right of every citizen to have access to the electricity system is guaranteed by Brazilian legislation. To overcome the problem of lack of access, electrification programs were created by the federal government to connect families to the electricity grid. The main project, entitled Programa Luz para Todos, has served more than two million families since its creation through the extension of the electrical grid system. However, it still have thousands of homes to be served, mainly in rural areas and communities in the Amazon, due to the impossibility of connecting by distance from urban centers, which makes access to essential services such as quality education and health unfeasible. In addition, isolated communities have as an option for this scenario diesel generation for electricity and the use of firewood and charcoal for food preparation, strengthening the use of non-renewable resources that harm the environment and raise family income expenses. Aiming to present a solution that guarantees electricity for residence in isolated areas, in order to provide a better quality of life and promote the use of renewable energies, the present case study aims to report the implementation of a photovoltaic solar system for energy generation electricity and a biogas system to generate cooking gas in a residence in the Três Unidos community, located in the rural area of Manaus, taking into account the characteristics of the resources present in the isolated community, allied to sustainable development. To meet the objectives, the method is based on the study of the development of hybrid microgrids using solar energy with biomass for communities in the Amazon and bibliographic reading of the implemented systems and their components, report of field visits carried out, and questionnaire applied to the resident. In this way, the study concludes that the use of renewable solutions in homes in rural communities presents itself as a solution to the problems of lack of electrification and costs of cooking gas due to the feasibility of the project due to the location (for solar energy) and natural resources (for biodigester), contributing to the positive impact on access to essential services and development of isolated regions.